A novel control strategy of regenerative braking system for electric vehicles under safety critical driving situations. (15th April 2018) - Qiu, Chengqun; Wang, Guolin; Meng, Mingyu; Shen, Yujie
Abstract: This paper mainly focuses on control strategy of the regenerative braking system of an electric vehicle under safety critical driving situations. With the aims of guaranteeing the electric vehicle stability in various types of tire-road adhesion conditions, based on the characteristics of an electrified powertrain, a novel control strategy of regenerative braking system is proposed for electric vehicles during anti-lock braking procedures. Firstly, the main construction of the case-study electric car with regenerative braking system is introduced. Next, based on the phase plane theory, the optimal brake torque is calculated for ABS control of an electric vehicle. Then, an allocation control, wherein the required optimal brake torque is divided into two parts that are disposed respectively by the friction and regenerative brakes, is discussed. In addition, two parameters for evaluating regeneration braking energy efficiency contribution while in the deceleration braking process are defined. Furthermore, a novel regenerative braking control strategy named "serial control strategy" is proposed. Finally, the road tests are implemented in four types of tire-road adhesion conditions under safety-critical driving situations. The test results validate the effectiveness and feasibility of the proposed control strategy. Highlights: A new control strategy of regenerative braking system for electric vehicles is proposed. Design of the regenerative braking system is introduced. Two different evaluation parameters for regenerative breaking energy efficiency contribution are defined. The control strategy and evaluation parameters are verified by road test results.